Cydia trogodana Prose, 1988, new for Italy, with notes on the Italian species of the Cydia succedana-group Denis & Schiffermiiller (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Cydia trogodana Prose, 1988, new for the Italian fauna, is reported. The species, foundin Cyprus and Greece, was collected in Sicily. Remarks on the species belonging to theCydia succedana-group Denis & Schiffermiiller in the Italian fauna Cydia succedana(Denis & Schiffermiiller, 1775), Cydia cytisanthana Burmann & Prose, 1988, Cydiaderrai Prose, 1988, Cydia ulicetana (Haworth, 1811 ), Cydia conjunctana (Moschler,1866), Cydia trogodana, Cydiaplumbiferana Staudinger, 1871, Cydia vallesiaca (Sauter,1968), Cydia intexta (Kuznetsov, 1962), Cydia medicaginis (Kuznetsov, 1962) and Cydiaalbipicta (Sauter, 1968) are given.
Keywords: Cydia trogodana; new record; succedana-group; Italy